Science Learning with VideoScribe-Based Learning Video for Elementary School Students - I Wayan Deni Perdana Putra; I Ketut Gading; I Ketut Dibia (Jurnal Ilmiah Sekolah Dasar, 2021)
There are still many teachers who do not manage to create a fun learning environment for students. Moreover, the lack of learning media makes it difficult for students to understand the learning material. This study aims to develop a learning video usingÂ the VideoScribeÂ app to facilitate students ' learning. Development research was employed in this study, while 4-D was used as the research model. One selected subject content expert, one selected learning design expert, one preferred learning media expert, and two chosen people for the individual trial became the subject of this study. Observation, interviews, and questionnaires had been utilized to collect the data. A questionnaire was the instrument used to gather the data. The validity of the study instrument was evaluated with the Gregory formula. The data were analyzed using qualitative descriptive statistics and quantitative descriptive statistics methods. The results showed that this study got a score of 1.00 with a very high product acceptability coefficient. It could be concluded that the developed media was feasible to be applied in learning. This study implied that the learning video made students more easily understand science subject matter.